Primary Breast Tumors with Mesenchymal Morphology - Tevatia, Manvir S.; Mishra, Prabhashankar; Baranwal, Ajay K.; Nichat, Prachi B.; Shelly, Divya; Awasthi, Shivali; Sengupta, Prashant (Journal of Laboratory Physicians, 2021)
Overview Mesenchymal tumors of the breast are rare. Few epithelial tumors also have mesenchymal components. It is crucial to identify these as per histogenesis. This can be facilitated by markers of epithelial–mesenchymal transition (EMT).Objectives The aim of this study was to categorize the breast lesions with mesenchymal morphology and to study EMT on immunohistochemistry (IHC).Materials and Methods This is a retrospective study of 5-year duration from January 2015 to December 2019. Inclusion criteria: all breast lesions showing mesenchymal/nonepithelial morphology, complete or partial, on histology. Exclusion criteria: Mammary carcinomas without any mesenchymal/nonepithelial morphology, fibroadenomas, and lymphomas. Demographics, clinical, gross examination, histology, and IHC findings of selected cases were reviewed and recorded. Three additional markers p53, E-cadherin, and β-catenin were performed.Statistical Analysis Used Frequency calculation for each variable (IHC).Results Thirteen (2.5%) out of total 510 breast specimens showed mesenchymal histology. Of these, five (38.5%) were metaplastic breast carcinomas (MBC), four (31%) were phyllodes tumor (PT), and one (7.7%) case each of malignant peripheral nerve sheath tumor, primary stromal sarcoma of breast, pseudoangiomatous stromal hyperplasia, and myofibroblastoma. Loss of E-cadherin was seen in 4/5 (80%) MBCs and was retained in ductal component of PTs. p53 was not expressed in any of the tumors except 3/5 (60%) MBCs. β-Catenin was aberrant in all MBCs.Conclusions Primary breast tumors with mesenchymal morphology present a spectrum ranging from benign mesenchymal, fibroepithelial neoplasms to malignant tumors of mesenchymal and epithelial origin. Loss of E-cadherin, expression of p53, and aberrant expression of β-catenin are suggestive of EMT and molecular heterogeneity of MBCs.
Keywords: metaplastic; mesenchymal; sarcoma; epithelial–mesenchymal transition